DEVELOPMENT OF VISCOSITY EQUATION OF STATE FOR ENVIRONMENTALLY FRIENDLY HFO REFRIGERANTS - Fachran Rafly, Achmad
Refrigerant’s viscosity is one of the most important property in refrigeration system design. This property affects heat transfer and momentum transport coefficient, pressure losses in the system, amongst other. However, viscosity of environmentally friendly refrigerants, such as hydrofluoroolefine (HFO), is not well understood due to the lack of measurement data. Therefore, other approach is needed to understand the viscosity of HFO. In the last few years, the effort to understand refrigerant’s viscosity is focused on the development of equation of state, or modelling. This approach gives well enough understanding of refrigerant’s properties with minimum measurement data availability, and is preferred due to its ready–to–use nature in simulation and database application programming. However, the published viscosity models of HFO have very different form for each refrigerant, and still have pretty significant deviations. Therefore, general equation of state which can represent multiple HFO refrigerants is highly needed. This study develops general form of viscosity equation of state for R-1336mzz(Z), R-1233zd(E), R-1234yf, dan R-1234ze(E) in liquid phase. The model is formulated based on extended corresponding state (ECS) method. Optimization of residual contribution model is processed with genetic algorithm based program and weighted least square linear regression. The value of average absolute deviation (AAD) from the proposed model is generally better than other model published earlier. The viscosity model for R-1336mzz(Z) has AAD value of 0.53% and STD value of 0.79% from 200 reference data. Viscosity model for R- 1233zd(E) has AAD value of 1.4% and STD value of 2.0% from 165 reference data. While viscosity model for R-1234yf has AAD value of 0.87% and STD value of 1.5% from 140 reference data. Finally the viscosity model for R-1234ze(E) has AAD value of 0.55% and STD value of 0.87% from 149 reference data.